Pengaruh Literasi Keuangan dan Tingkat Pendidikan Terhadap Inklusi Keuangan Masyarakat Di Desa Sukarara - Putri, Nunung Isna; Isnawati, Isnawati (Universitas Hamzanwadi, 2025)
This study aims to determine the effect of Financial Literacy and Education Level on Financial Inclusion of the Community in Sukarara Village. The population in this study were all weaving business actors in Sukarara Village, while the sample of this study was 97 Business Actors. This type of research is associative research. Data processing in this study used IBM SPSS 26 for Windows, where classical assumption tests, multiple linear regression tests, coefficients of determination, and hypothesis tests were carried out. Based on the results of the analysis, the variables Financial Literacy and Education Level have a positive and significant effect on Financial Inclusion of the Community in Sukarara Village. Based on this, it is recommended that business actors in Sukarar Village can improve Financial Literacy and Education Level to increase Financial Inclusion of the Community in Sukarara Village.